The effect of natural Zeolite (Ag-Zeolite) modified with silver against the inhibition of Candida albicans - Catur SEPTOMMY; Nikmatus SA’ADAH; Binti MU’AROFAH (Dentistry Faculty, 2020)
Candida albicans is a commensal microorganism or normal flora in the mouth, and about 20-75% is found in the general population without causing symptoms (Candida carriers). C. albicans is a primer agent that cause oral candidiasis. Silver modified natural Zeolite has potential antifungals. This research aimed to know the effect of silver modified natural Zeolite (Ag-Zeolite) on the C. albicans growth. Antifungals were treated through a good diffusion test. Antifungals agents were divided into four groups. They were 30 mg with 0.025 M (AgNO3), 0.05 M (AgNO3), 0.1 M (AgNO3) modified natural zeolite, and unmodified natural zeolite. Each group has treated into four times well diffusion tests. This research showed that 0.1 M (AgNO3) modified natural Zeolite has the highest inhibition. ANOVA test showed the average diameter of inhibition was significant in 0,004 (p0,05). Each group has different average diameter inhibition. In conclusion, the active natural Zeolite with silver modification can inhibit the growth of C. albicans better than natural Zeolite without silver modification